Pandemic H1N1 Influenza Infection and Vaccination in Humans Induces Cross-Protective Antibodies that Target the Hemagglutinin Stem - Thomson, Christy A.; Wang, Yanni; Jackson, Linda; Olson, Melanie; Wang, Welson; Liavonchanka, Alena; Keleta, Liya; Silva, Vanessa; Diederich, Sandra; Jones, R B.; Gubbay, Jonathan; Pasick, John; et al. (Frontiers in Immunology, 2012)
Most monoclonal antibodies (mAbs) generated from humans infected or vaccinated with the 2009 pandemic H1N1 (pdmH1N1) influenza virus targeted the hemagglutinin (HA) stem. These anti-HA stem mAbs mostly used IGHV1-69 and bound readily to epitopes on the conventional seasonal influenza and pdmH1N1 vaccines. The anti-HA stem mAbs neutralized pdmH1N1, seasonal influenza H1N1 and avian H5N1 influenza viruses by inhibiting HA-mediated fusion of membranes and protected against and treated heterologous lethal infections in mice with H5N1 influenza virus. This demonstrated that therapeutic mAbs could be generated a few months after the new virus emerged. Human immunization with the pdmH1N1 vaccine induced circulating antibodies that protected mice from lethal, heterologous H5N1 influenza infections. We observed that the dominant heterosubtypic antibody response against the HA stem correlated with the relative absence of memory B cells against the HA head of pdmH1N1, thus enabling the rare heterosubtypic memory B cells induced by seasonal influenza and specific for conserved sites on the HA stem to compete for T-cell help. These results support the notion that broadly protective antibodies against influenza would be induced by successive vaccination with conventional influenza vaccines based on subtypes of HA in viruses not circulating in humans.